Location of foreign direct investment in a regional integration area - Pontes, José Pedro (2022)
In a regional integration area two processes take place simultaneously: the fall of trade costs and the regional convergence of per capita of the countries. The impact of these trends upon the location of the productive activity is examined through a static two person noncooperative game where each player(firm)selects one of three spatial strategies: to locate a single plant in the large country; to locate a single plant in the small country; and to settle a multiplant firm in the two countries. It can be inferred that to locate a plant in the small country is always a dominated strategy. The degree of symmetry in market size in the two countries appears as the major factor of the feasibility of production in the small peripheral economy.On the other hand, the fall of trade costs has a sensible impact upon the location of production only for intermediate levels of regional convergence. The "tariff jumping" argument for FDI has a limited field of application.